The Effect of Addition of Rebonized Shrimp (Mysis relicta) to Commercial Feed on the Quality of Fish Color Platy Mickey Mouse (Xiphophorus maculatus) - Hafizah Hafizah; Mulyadi Mulyadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Production ornamental fish in Indonesia, especially freshwater aquaculture has become an important livelihood for the community and is one alternative to increase the production of Indonesian ornamental fish exports. One of the fish that has the potential to be developed because this fish is one of the popular fish for fish lovers and has economic value is the Platy Mickey Mouse (Xiphophorus maculatus) fish. Color is one of the reasons for ornamental fish that is in demand by the community, so that farmers need to maintain the color of ornamental fish by feeding them with color pigments. Rebon shrimp flour (Mysis relicta) plays a good role in fish coloring because it contains astaxsanthin carotenoids. This study aims to determine the effect of the addition of rebon shrimp flour with different doses on the quality of the color of Platy mickey mouse fish. The method used in this study is the experimental method and the design used is a completely randomized design (RAL) of 1 factor with 4 levels of treatment and 3 (three) times of repetition, thus there are 12 units of experiment. The treatment in this study are: P0 = Feed without mixture of rebon shrimp (control), P1 = Addition of 5% rebon shrimp flour to feed, P2 = 10% addition of rebon shrimp flour in feed, P3 = Addition of 15% rebon shrimp flour to feed. Platy mickey mouse fish seeds which are used 2-3 cm in size are stocked in an aquarium with a volume of 7 liters of water / aquarium and the stocking density of each container is 6 tails. Maintenance lasts for 40 days and feed is given by adsatiation, feeding frequency 3 times a day. Parameters observed include changes in color quality, absolute weight growth, absolute length, survival rate and water quality. The results showed that the addition of rebon shrimp flour to feed significantly affected the color increase in Platy mickey mouse fish seeds (Xiphophorus maculatus), where the treatment of P3 (15% rebon shrimp flour) was able to increase the color 12.91 ± 0.69, but did not significantly affect weight growth absolute and absolute length growth of the fish Platy Mickey Mouse (Xiphophorus maculatus). Keywords: staining; Commercial Feed; Rebon Shrimp (Mysis relicta); Platy Mickey Mouse Fish (Xiphophorus maculatus).